The anniversary of the military coup attempt in Turkey, July 15–16, 2016. The evolution of a political system - Y. S. Kudryashova (Международная аналитика)
During the government of AK Party army leaders underprivileged to act as an exclusive guarantor preserving a secular regime in the country. The political balance between Secular and Islamite elites was essentially removed after Erdogan was elected Turkish President. Consistently toughening authoritarian regime of a ruling party deeply accounts for a military coup attempt and earlier periodically occurred disturbance especially among the young. The methods of a coup showed the profundity of a split and the lack of cohesion in Turkish armed forces. Erdogan made the best use of a coup attempt’s opportunities to concentrate all power in his hands and to consolidate a present regime. The mass support of the population during a coup attempt ensured opportunities for a fundamental reorganization of a political system. Revamped Constitution at most increases political powers of the President.